Ba ancaloit khung indol từ cây trang nam (Kopsia pitardii Merr.) - Thu Hương, Đỗ Thị; Hạnh, Nguyễn Ngọc; Chiến, Nguyễn Quyết (Vietnam Journal of Chemistry, 2014)
Three monoterpenoid indole alkaloids: methyl 11, 12-methylenedioxy-N1-decarbomethoxy-∆14,15-chanofruticosinate (1), methyl N1-decarbomethoxychanofruticosinate (2), methyl 11,12-methylenedioxychanofruticosinate (3) were isolated from dried leaves of the Vietnamese medicinal plant Trang-Nam (Kopsia pitardii Merr., Apocynaceae) with 0.12, 0.038 and 0.005% yields, respectively. Their structures were determined by MS and NMR means.